2019
DOI: 10.1038/s41386-019-0551-0
|View full text |Cite
|
Sign up to set email alerts
|

A multipredictor model to predict the conversion of mild cognitive impairment to Alzheimer’s disease by using a predictive nomogram

Abstract: Predicting the probability of converting from mild cognitive impairment (MCI) to Alzheimer’s disease (AD) is still a challenging task. This study aims at providing a personalized MCI-to-AD conversion estimation by using a multipredictor nomogram that integrates neuroimaging features, cerebrospinal fluid (CSF) biomarker, and clinical assessments. To do so, 290 MCI patients were collected from the Alzheimer’s Disease Neuroimaging Initiative (ADNI), of whom 76 has converted to AD and 214 remained with MCI. All su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 47 publications
1
57
0
Order By: Relevance
“…Many studies have reported improvements in the predictive accuracy in models combining radiomic features or signatures with clinical risk factors ( 22 , 36 38 ). For example, the nomogram models developed by combining radiomic signatures and clinical factors have shown outstanding performance in the prediction of cognitive impairment ( 37 ) and in the differentiation of renal angiomyolipoma ( 38 ). This strategy was adopted in the present study and a radiomics nomogram was developed by incorporating the radiomics signature into the clinical nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported improvements in the predictive accuracy in models combining radiomic features or signatures with clinical risk factors ( 22 , 36 38 ). For example, the nomogram models developed by combining radiomic signatures and clinical factors have shown outstanding performance in the prediction of cognitive impairment ( 37 ) and in the differentiation of renal angiomyolipoma ( 38 ). This strategy was adopted in the present study and a radiomics nomogram was developed by incorporating the radiomics signature into the clinical nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the selected features of the T1WI and T2WI sequences (p < 0.05) were combined as the T1-2WI features. All of the retained T1WI, T2WI and T1-2WI features were processed by dimensionality reduction using the LASSO method to improve the accuracy and degree of modelling fit [20]. Data within 1-standard error of the minimum criterion measure were used in this study.…”
Section: Radiomics Feature Selectionmentioning
confidence: 99%
“…Some studies revealed that a high-level latent feature learned from deep neural network could be potential tool for the diagnosis of AD and its prodromal stage, MCI 21 23 . Most studies using texture analysis or radiomics approaches have focused on the discrimination of diagnostic groups or the prediction of conversion to dementia 24 26 .…”
Section: Introductionmentioning
confidence: 99%